Descriptive Study on Benchmarking of the Results from the Performed Activities in the Preventive Medicine in Schools in Some Regions of Republic of Bulgaria - J. Staykova; R. Chilingirova (Challenges in Disease and Health Research Vol. 5, 2021)
Introduction: The policy for effective functioning of maternity, child and school healthcare comprises actions for integrated approach of the institutions and publicity for children’s health. The health status of the population mostly depends on factors, whose influence starts in childhood. It is also a reflection of the statement that the cares for children’s health are investment in future healthy generations, as in childhood are set the foundations for human health and is formed the health behaviour of each person, which ensure higher quality of life and health of the national human capital. A significant and permanent limitation of the pandemic of chronic and other diseases may be expected by health promotion and preventive measures which were taken in early childhood, because of their radical and long–term effect. The purpose of the present work is to study the health and dental status of pupils aged between 7 and 15 from municipality of Kardzhali and Sandanski by benchmarking. Materials and Methods: There are included in the survey schools from municipality of Kardzhali and Sandanski, determined by the method of random selection. The survey comprises 1594 children aged between 7-15. The examinations were performed by physician-specialists: A paediatrician, an otorhinolaryngologyst, an ophthalmologist and a dentist. For registration of the data from the prophylactic examinations are used “Dental Treatment/ Examination Form” and “Medical History and Screening Form”. For the statistical processing of the data there is used the Fisher’s criterion. Results and Discussion: The comparative analysis of the results for health and dental status of the examined children from municipality of Kardzhali and Sandanski shows statistically significant difference in the early development of the children from the two municipalities in favour of the children from municipality of Kardzhali (94% against 1% for Sandanski). There is a significant difference between them concerning allergies, respectively 1.38% and 15.44%. There were also reported the diseases (Heart Diseases and Diabetes) of children from Kardzhali. The examination by physician-otorhinolaryngologyst shows significantly lower levels of all indicators of the examined children from Kardzhali. The visual acuity of the children from Kardzhali is with better values in comparison to the children of Sandanski, respectively 79% against 64%. The main share of the cases with colour deficiency is also lower in Kardzhali-0.13% against 1.29%. The cases of esotropia/exotropia show higher levels of the examined patients in Kardzhali (4% against 0.4%). As a whole the dental status of the children from Kardzhali is better (64% against 53%), but by indicators: presence of caries, gingivitis and orthodontic problems are observed more favourable values of the children from Sandanski. Conclusion: The showed results are disturbing and it is necessary to develop intervention program, which include preventive actions with focus on health promotion and health changes in the environment and way of life of children.